If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -1x + 10 Multiply f * x fx = -1x + 10 Reorder the terms: fx = 10 + -1x Solving fx = 10 + -1x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 10x-1 + -1 Simplifying f = 10x-1 + -1 Reorder the terms: f = -1 + 10x-1
| 10x^3-25x^2+20= | | 3(y+5)=32 | | 5m+5.25=42.75 | | -1-2g=1 | | -20+12r+6q-2r-3q-26= | | 0/27=x | | 2(a+2b)-(a-b)= | | 9+4r=1 | | 19=19h-19 | | 5=v+1 | | 1/6d+2/3=1/4(d-2) | | -4+15=11 | | sinA=0.5 | | 7x-8-5x=0 | | 118=-5(-4-4p)-6p | | -4+15=x | | 7c-2c=42 | | x-6-17=-13 | | -7z+4+16-8z= | | X^3-6x+10x-8=0 | | 15=12k-9 | | a+(a+10)=16 | | -4c+9(3c+5)= | | 10p+18=-12 | | 13q+48=-3q | | -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 | | x-2(6.5+3.5x)=11 | | -9(5+2f)= | | -5x-7x+3+6= |